The glory of God in the face of Jesus Christ : deification of Jesus in early Christian discourse - Bernard, David K., 1956- (Journal of Pentecostal Theology Supplement Series, 2016)
There is now a substantial scholarly consensus for the emergence of a high or divine Christology very early and from a Jewish context, but the questions of \'how\' and \'why\' need further study. Within the framework of traditional Jewish monotheism, Paul and other early Christians used the language of deity to describe Jesus. To investigate their view of Jesus, the author examines Paul's discourse in 2 Cor 3:16-4:6, employing insights from rhetorical criticism and Oneness Pentecostal Christology. He explains how early Christians proclaimed the deity of Jesus within their monotheistic Jewish context. He then identifies socio-rhetorical reasons for and practical consequences of the monotheistic deification of Jesus.